PUBLIC SERVICE IN THE REPUBLIC OF KAZAKHSTAN IN THE LIGHT OF PRESIDENT’S ONE HUNDRED STEPS THE MAIN DIRECTIONS OF IMPROVEMENT - Leila, Жанузакова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In the research paper are considered the main directions developing of Kazakhstan public service in connection with the plan of the President “One hundred steps to implement five institutional reforms”. The analysis of the current legislation is conducted and problems of its improvement are identified.